Analisis Kepuasan Pelanggan Terhadap Layanan Jasa Pengiriman Sicepat Ekspress - Gaizka Aqshal Razzandi Suryaningrat; Najla Saifana; Tesar Agnia Arifian; Maulana Ikhsan Yazid; Siti Sahara (Peneliti.net, 2023)
This study aims to determine the effect of customer satisfaction on SiCepat Ekspress delivery services. This study uses a quantitative approach. Quantitative research aims to develop a mathematical model, where this research does not only use theory taken from literature or theoretical studies, but it is also very important to build hypotheses that have a connection with the natural phenomena to be studied. The direction and focus of the research are aimed at describing and describing objectively and logically the characteristics of the phenomenon or social symptoms studied in this case is the quality of SiCepat Ekspress delivery services for the Rawamangun Branch. The data collection technique uses a questionnaire that has been tested for validity and reliability.